PENERAPAN METODE WAFA DALAM MENINGKATKAN KEBERHASILAN PROGRAM TAHFIDZUL QUR’AN DI SEKOLAH DASAR ISLAM MOHAMMAD HATTA MALANG - As'ari, Hasyim; Saiban, Kasuwi; Umi Salamah (STAI Ma'had Aly Al-Hikam Malang, 2025)
This study aims to analyze in depth the implementation and success of the WAFA method in the Tahfidzul Qur'an program at Mohammad Hatta Islamic Elementary School, Malang. The WAFA method is an innovation in Qur'anic learning based on right-brain optimization, utilizing the TANDUR strategy and a multisensory approach. The research employed a descriptive qualitative approach, with data collected through participatory observation, in-depth interviews, and documentation studies during the period of October–December 2021. The results showed that the implementation of the WAFA method was effective, carried out through five structured stages (5P) with an emphasis on the Hijaz rhythm and meaningful movements. Approximately 78.3% of fifth and sixth-grade students successfully memorized the entire juz 30, indicating a significant improvement compared to the previous method. This success is influenced by factors such as teacher creativity, a conducive learning environment, and systemic school support. The findings provide a theoretical contribution to the development of neuroscience-based Qur'anic learning methods and practical implications for managers of Islamic educational institutions. It is recommended that teacher training modules be developed and technology integrated into the implementation of the WAFA method.